Engineering nanointerfaces of Cu-based catalysts for balancing activity and stability of reverse water-gas-shift reaction. (May 2023) - Zhang, Ling; Yu, Jiafeng; Sun, Xingtao; Sun, Jian
Abstract: The strong metal support interaction (SMSI) is an important concept in heterogeneous catalysis and has been widely used to stabilize metal nanoparticles by inducing nanointerfaces between metal and support. Although many considerable signs of progress have been achieved in the SMSI establishment, the control of the nanointerfaces is barely studied, leading to inevitably sacrificed catalytic activity due to the excessive coverage. Herein, we investigated multiple strategies to effectively regulate nanointerfaces from different aspects, such as support composition, parameters of Cu preparation, pre-treatments and reaction conditions, to balance the activity and stability of Cu/TiO2 catalysts over reverse water-gas-shift (RWGS) reaction. It reveals that only Zn doping in TiO2 support can suppress the formation of nanointerfaces during reduction treatments due to the restraint of both TiO2 reducibility and electron transfer from TiO2 to Cu. The dynamic evolution of nanointerfaces is observed with the RWGS reaction conditions and finally reaches a stable state. The coverage of Cu that supported on the Zn-modified TiO2 significantly declined, resulting in a 44% increment in catalytic activity without sacrificing their stability at 700 °C. The proposed strategies on the nanointerfaces regulation can provide guidelines for balancing the activity and stability of catalysts from the aspects of catalyst design and conditions engineering. Graphical Abstract: ga1 Highlights: Multi-dimensional regulation strategies of nanointerfaces on Cu-based catalysts is proposed. A linear correlation between TiO2 reducibility and its coverage over Cu is revealed. Zn dopant could suppress the SMSI by inhibiting the electron transfer from TiO2 to Cu. Activity and stability over the RWGS reaction are balanced on Zn-doped Cu/TiO2 catalyst.